Corticosteroids use and neurocognitive functioning in patients with recurrent glioblastoma: Evidence from European Organization for Research and Treatment of Cancer (EORTC) trial 26101. Issue 4 (13th March 2022) - Caramanna, Ivan; de Kort, Julie M; Brandes, Alba A; Taal, Walter; Platten, Michael; Idbaih, Ahmed; Frenel, Jean Sebastien; Wick, Wolfgang; Preetha, Chandrakanth Jayachandran; Bendszus, Martin; Vollmuth, Philipp; Reijneveld, Jaap C; et al.
Abstract: Background: In patients with recurrent glioblastoma, corticosteroids are frequently used to mitigate intracranial pressure and to improve patient neurological functioning. To date, in these patients, no systematic studies have been performed to assess neurocognitive functioning (NCF) in relation to corticosteroid treatment. Methods: Using baseline data (ie, prior to randomization) of European Organization for Research and Treatment of Cancer (EORTC) trial 26101, we performed regression analysis to assess the predictive value of corticosteroid intake on performance of the EORTC brain tumor clinical trial NCF test battery. The battery is comprised of the Hopkins Verbal Learning Test—Revised (HVLT-R), Controlled Oral Word Association Test (COWA), and Trail Making Test (A and B). Results: Out of 321 patients, 148 (46.1%) were not using corticosteroids, and 173 were using dexamethasone (34.3%), methylprednisolone (9.7%), or other corticosteroids (9.9%). Patients on corticosteroids had worse performance on all neurocognitive tests. Regression analyses demonstrated a negative association between corticosteroids use and the HVLT-R free recall score ( R 2 change = 0.034, F change (1, 272) = 13.392, P < .001) and HVLT-R Delayed Recall score ( R 2 change = 0.028, F change (1, 270) = 10.623, P = .002). No statistically significant association was found for HVLT-R Delayed recognition, COWA, TMT part A and TMT part B ( P > .05). Conclusions: Glioblastoma patients prescribed with corticosteroids show poorer memory functions, expressive language, visual-motor scanning speed, and executive functioning than patients not using corticosteroids. Furthermore, we found a negative association between corticosteroid intake and memory functions. The possibility of deleterious effects of corticosteroids on NCF should be considered during clinical decision making.